Analisis Peran Kepala Sekolah sebagai Manajer bagi Guru SMP Katolik Ambon - Emanuel Norberus Do; Theresia Laurens; Lamberthus Johannes Lokollo (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
This study is motivated by the crucial role of principals in ensuring the continuity of managerial functions in schools, particularly at SMP Katolik Ambon, which faces various challenges in educational management. The research aims to describe the principal's efforts in overcoming obstacles to managerial functions through participatory and collaborative leadership approaches. The study employed a qualitative method using observation, interviews, and documentation techniques involving the principal, vice principal, civil servant teachers, and foundation-based teachers. The findings indicate that the principal successfully addresses resource, communication, and coordination constraints through mentoring strategies, clear task distribution, and enhanced teacher participation. This study demonstrates that the principal’s contribution not only strengthens school management but also fosters a more adaptive culture of collaboration. The implications highlight the importance of developing school leadership capacity and recommend strengthening policy and facility support to optimize managerial functions.